UV LED disinfection as a novel treatment for common salmonid pathogens - Kyle D. Rauch; Jessica L. Bennett; Amina K. Stoddart; Graham A. Gagnon (Scientific Reports)
Abstract Aeromonas salmonicida and Yersinia ruckeri are common pathogenic bacteria that impact salmonid aquaculture. Although vaccinations are available against both organisms, large-scale vaccination efforts can be expensive, cumbersome, and are not always reliable. Alternatively, these pathogens have been effectively inactivated using UV radiation from mercury-based systems. These systems are energy intensive and fragile which currently limits their use to closed and semi-closed production systems. UV light emitting diodes (UV LEDs) have recently emerged as a novel alternative to traditional mercury-based treatment. UV LEDs have durable housing, a relatively low energy draw, can be powered by a battery source and are adaptable to challenging environments. This study examined the effectiveness of three UV LED wavelengths for disinfection of A. salmonicida and Y. ruckeri in pure culture and resuspended in a wastewater matrix. All tested UV LEDs were effective in disinfecting both organisms. 267 and 279 nm wavelengths outperformed 255 nm disinfection in both test matrices. Particulate matter from wastewater reduced the upper limit of treatment for A. salmonicida but results still indicated that all wavelengths were effective for disinfection in a challenging matrix. This study represents the first use of UV LEDs for disinfection of A. salmonicida and Y. ruckeri and provides impact to aquaculture producers looking to implement novel technologies for disease control.